Peers and offender decision‐making - Hoeben, Evelien (Criminology & public policy, 2019)
Offender decision‐making generally occurs in social context. In this article, we discuss the potential for integrating insights on peer processes and decision‐making processes to advance our understanding on the decision to engage in crime. In particular, we address the developmental and situational influence of peers on perceptions, preferences, and dual‐systems processing. We contribute to this literature by elaborating on situational peer processes and discuss the ways in which peers can affect decision‐making through their mere presence as well as through their active involvement as instigators, conversational partners, and co‐offenders.